Implementasi Metode Multi-Attribute Utility Theory Dalam Menentukan Karya Terbaik Proyek Yuwana Wikimedia - Muhammad Ikhlas; Rio Bayu Sentosa (CogITo Smart Journal, 2024)
Reading activities are a form of literacy that can foster societal development. We can encounter various short forms of literacy besides reading and writing books, such as novel reviews, communicating and cross-talking. “However, there is still limited access to platforms that support literacy activities, particularly those that encourage community storytelling”. The Yuwana Project is one of the competitions held by Wikimedia Indonesia to provide space for people to work on writing children's short stories and traditional game stories. This competition is held online via Wikibuku. Where participants who take part in this competition will be assessed to determine the best work. The assessment process needs to be thorough so that those assessed comply with the assessment criteria that have been determined. For this reason, there is a need for a method that can produce the best decisions. The Multi-Attribute Utility Theory (MAUT) method is a method for making decisions by identifying and analyzing several variables quantitatively, In this study, 10 alternative data were tested, where the results were A6 with a preference value of 0.65 with the best first rank, then A7 with a preference value of 0.62 ranked second, and A2 with a preference value of 0.60 ranked third. So that the MAUT method can provide recommendations for selecting the best work for the Yuwana Wikimedia project.